Adherence to Gluten-free Diet in a Celiac Pediatric Population Referred to the General Pediatrician After Remission. Issue 1 (July 2020) - Sbravati, Francesca; Pagano, Sara; Retetangos, Cristiana; Spisni, Enzo; Bolasco, Giulia; Labriola, Flavio; Filardi, Maria C.; Grondona, Ana G.; Alvisi, Patrizia
ABSTRACT: Objectives: Assessment of adherence to gluten-free diet in celiac disease (CD) is generally recommended. Few data are available about consequences of transition from the referral center to the general pediatrician (GP) once remission is achieved. Methods: Adherence was assessed in patients referred to the GP for an annual basis follow-up, called back for re-evaluation. Immunoglobulin A (IgA) antitissue transglutaminase (anti-tTG) antibodies and the Biagi score (BS) were determined at last follow-up at the referral center (V1), and at re-evaluation (V2). Patients were classified as adherent (BS 3–4, IgA anti-tTG <7 U/mL) and nonadherent (BS 0–2, IgA anti-tTG ≥7). Scores of adherence were correlated with personal and clinical data. Results: We evaluated 200 patients. Overall, we found good adherence rates in 94.95% of patients at V1 and 83.5% at V2. IgA anti-tTG were negative in 100% at V1 and 96.97% at V2. BS is 3 to 4 in 94.5% at V1 and 84% at V2. Adherence at V2 was significantly worse than V1 ( P   <  0.001). No significant associations were found between scores of adherence and sex, symptoms and age at diagnosis, family history of CD, comorbidity, and diagnosis by endoscopy. Age 13 years or older represents a risk factor for lack of compliance at V1 ( P   =  0.02) and V2 ( P   =  0.04), and foreign nationality at V2 ( P   =  0.001). Conclusions: The BS, serology, and a clinical interview, integrated, are reliable tools for assessing pediatric adherence to gluten-free diet. We argue that referring patients to the GP after remission of CD is important, but the process must be improved and recommendations are required.